(untitled) (Eurasian Research Bulletin, 2022)
In today’s conditions of increasing competition in world markets, it is of utmost importance to fundamentally increase the competitiveness of our economy, to strengthen support for enterprises that produce products for export, and to comprehensively encourage the participation of farms, small businesses and private enterprises in export activities. In this article, the theoretical foundations of improving the organizational and economic mechanism of management of food industry enterprises were analysed and conclusions and recommendations were given.